Co-occurrence of Myasthenia Gravis and Multiple Sclerosis: A Case Report - Rynkevič, G.; Kizlaitienė, R. (Neurologijos seminarai, 2024)
Myasthenia gravis (MG) and multiple sclerosis (MS) are thought to have a common autoimmune mechanism as the number of reported co-occurrences of both diseases is increasing. The involvement of both T cells and B cells in the pathogenesis of these two diseases is suspected. As the symptoms and clinical course of MS and MG can be similar in some cases, this makes it difficult to consider the possibility of the coexistence of these disorders. However, laboratory and imagining findings are helpful in distinguishing both diseases and differentiating them from other neurological conditions. Additionally, there can be obstacles in effective treatment selection for patients with MS and MG coexistence. This article presents a clinical case of a woman with previously diagnosed MG who was admitted to hospital 12 years later with new-onset symptoms and was additionally diagnosed with relapsing-remitting multiple sclerosis (RRMS). Remission of MG was achieved with medications and thymectomy, but treatment of MS had its challenges, as first-line immunomodulating drugs interferon beta-1a and dimethyl fumarate were not effective, and second line treatment with monoclonal antibody medication rituximab and ocrelizumab showed efficacy for both diseases, MG and MS. The presented case highlights the importance of considering a manifestation of another disease when treating an already diagnosed disorder. It also emphasizes the importance of further research into the relationship between MG and MS.